STATISTICAL ANALYSIS OF MALAY MANUSCRIPTS IN THE BRITISH LIBRARY’S ONLINE COLLECTION FROM THE 17TH TO THE 19TH CENTURIES - Syed Najihuddin Syed Hassan; Nurul Izzatul Huda Mohamad Zainuzi; Abdulloh Salaeh; Nidzamuddin Zakaria; Nurul Syakirah Muhamad Sukri; Muhamad Syafiq Sahrol; Puteri Nurul Afiqah Mohd Hamdan (Journal of Islamic, Social, Economics and Development, 2022)
Malay Manuscripts are handwritten documents in Malay written in Jawi script that date from the early 14th century to the early 20th century. This study is a statistical assessment of a collection of Malay manuscripts published online at the British Library website between the 17th and 19th centuries. The researcher obtained codicology data for Malay manuscripts from the website. The goal of this study was to describe the codicology pattern of Malay manuscripts published on the website and conduct a statistical analysis based on the data gathered. To accomplish this goal, researchers choose quantitative analyses that are relevant to the study. According to the findings of the study, the codicology pattern of Malay manuscripts on the website can be divided into ten categories. The total number of manuscripts is 126, with the majority of Malay manuscripts dating from the 18th century accounting for 63.49% of the total. The majority of the manuscripts, 81%, are complete, and 63.5% are written in Malay. Furthermore, Khat Farisi recorded a percentage of 28.59%, European paper was the most popular type of paper with 37.3%, and black ink was the most popular with 50% usage. 47.62% are without catchwords, and 54% with no watermarks.